Expectation And Perception Of Homeowners On Service Quality Of Green Home Property Developers - Jayasingham, J. Pathma Priya (2023)
In this research, service quality analysis was conducted on homeowners who lived in green homes which was built by a green home property developer in Penang. In order to evaluate the service quality, a methodology that was developed by Parasuraman, Zeithaml & Berry in 1985 was adopted which is known as Servqual.